Group identity and civil-military relations in India and Pakistan - Williams, Brent Scott (Kansas State University, 2019)
This dissertation asks why a military gives up power or never takes power when conditions favor a coup d’état in the cases of Pakistan and India. In most cases, civil-military relations literature focuses on civilian control in a democracy or the breakdown of that control. The focus of this research is the opposite: either the returning of civilian control or maintaining civilian control. Moreover, the approach taken in this dissertation is different because it assumes group identity, and the military’s inherent connection to society, determines the civil-military relationship. This dissertation provides a qualitative examination of two states, Pakistan and India, which have significant similarities, and attempts to discern if a group theory of civil-military relations helps to explain the actions of the militaries in both states. Both Pakistan and India inherited their military from the former British Raj. The British divided the British-Indian military into two militaries when Pakistan and India gained Independence. These events provide a solid foundation for a comparative study because both Pakistan’s and India’s militaries came from the same source. Second, the domestic events faced by both states are similar and range from famines to significant defeats in wars, ongoing insurgencies, and various other events. In short, the theory developed suggests that Pakistan’s military has repeatedly given up power because domestic cleavages caused a perception among the civilian population that the military leader should transfer power or meet other political demands. Because the military’s leadership originates from the population, that leadership identifies with the perception of the group or groups that produce the leadership. Moreover, because the military leadership is homogenous, there is limited diversity in the military leadership’s perception of a domestic cleavage and there are no other security organizations preventing the military’s actions. Conversely, in India, a more diversified military leadership and a non-unified security apparatus serve to prevent action. This dissertation examines the historical record in both states’ timelines to determine if a group theory of civil-military relations explains the actions or non-actions of both militaries. The findings largely fit the developed theory.
Keywords: India; Civil-military relations; Group identity; South Asia; Pakistan; Military to civilian transition of power